Self-Report Assessment of Sexual Function After LEEP in Women who Report Negative Outcomes. (1st August 2022) - Giovannetti, O; Tomalty, D; Greco, S; Adams, M
ABSTRACT: Introduction: The Loop Electrosurgical Excision Procedure (LEEP) is a fast and highly effective method of removing cervical dysplasia. Interestingly, it has been reported that a subpopulation of women have negative symptoms post-LEEP, including significant decreases in arousal, lubrication, and orgasm satisfaction. There is discord surrounding the role of the cervix in sexual responses that has likely resulted in a lack of physician-patient communication regarding possible risks of female sexual dysfunction (FSD) after cervical procedures, such as the LEEP. Barriers to discussion may include a lack of standardized sexual health care pre- and post-operatively, lack of FSD resources, and inconsistent practices regarding patient-centered care and open conversations. Our study proposes that the symptom profile of women who have post-LEEP FSD is not only unique, but that it may be revealed by pre-and post-operative assessment using existing validated surveys as well as through open conversations. Objective: This study defines a symptom profile of patients who report negative post-LEEP outcomes related to FSD. It also determines whether a combination of validated self-report surveys and open conversations could elucidate FSD concerns pre- and post-operatively. Methods: First, a self-report survey was developed by researchers that included questions regarding locations of sexual responses and barriers to sexual health conversations; the full FSFI was included as a discrete component of the survey. Sixty-four participants were recruited from online patient groups, completed the online surveys, and were subsequently interviewed by the research team. The semi-structured interview protocol that was developed aimed to construct a narrative from women who report FSD following LEEP to develop an understanding of the language they use to describe their distress and dysfunction. The responses elucidated from these conversations were transcribed, and qualitative analysis was performed using NVivo12. Results: Our study validated the results from previous studies with regards to the existence of a subpopulation of women who report FSD following LEEP using self-report surveys. However, this study is the first to report a unique symptom profile of post-LEEP FSD patients that was not detected using existing validated tools such as the FSFI. Participants consistently described symptoms of altered or loss of cervical sensation during sex (numbness), pain with vaginal penetration, decreased lubrication, depression, loss of interest, arousal, desire, self-confidence, as well as issues with partners. Participants also described inadequate or absent pre-operative care regarding the disclosure of possible risks as well as screening for FSD. Post-operative care was reported to be minimal, with most patients feeling uncomfortable discussing sexual health concerns with their care providers. Patients also described a lack of resources available to them after LEEP, though they wished their physicians had provided them with this information. Conclusions: This study identifies a unique symptom profile of women who reported negative post-surgical outcomes which is distinct from symptoms previously reported by validated FSD screeners, an area which has not been researched sufficiently within the focus of LEEP. This study may inform future investigations targeting the development and administration of FSD assessment tools to standardize LEEP counselling and thereby improve patient outcomes. Disclosure: No